ФОРМИРОВАНИЕ КОММУНИКАТИВНОЙ КОМПЕТЕНЦИИ БУДУЩИХ СПЕЦИАЛИСТОВ ВОДНОГО ХОЗЯЙСТВА - Киличева, Ф.Б. (SCIENCE and SOCIETY, 2024)
The article discusses modern aspects of developing competencies in vocational education. The formation of communicative competence of students plays a key role in the overall process of professional training of a specialist. Communicative competence is a measure of students’ mastery of knowledge, skills and abilities in the field of communication at a level sufficient for their effective use in the process of solving professional problems.
Keywords: competence; competency; key competencies; competency-based approach; communicative approach; professionalism